2005
DOI: 10.1016/j.cell.2005.05.024
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Interactions of ATP with the AAA+ ClpX6 Unfoldase: Allosteric Control of a Protein Machine

Abstract: ATP hydrolysis by AAA+ ClpX hexamers powers protein unfolding and translocation during ClpXP degradation. Although ClpX is a homohexamer, positive and negative allosteric interactions partition six potential nucleotide binding sites into three classes with asymmetric properties. Some sites release ATP rapidly, others release ATP slowly, and at least two sites remain nucleotide free. Recognition of the degradation tag of protein substrates requires ATP binding to one set of sites and ATP or ADP binding to a sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

24
163
2
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(194 citation statements)
references
References 42 publications
24
163
2
2
Order By: Relevance
“…Studies on a related ATPase ClpX demonstrated complex allosteric linkages between multiple ATP-binding sites resulting in positive as well as negative cooperativity in ATP binding. 22 As it is not known which binding mechanism applies to nucleotide interactions with 12 sites in the hexameric ClpB, we restrict our analysis to observing the shape of binding isotherms to obtain information on the effective nucleotide-binding capability of ClpB.…”
Section: Resultsmentioning
confidence: 99%
“…Studies on a related ATPase ClpX demonstrated complex allosteric linkages between multiple ATP-binding sites resulting in positive as well as negative cooperativity in ATP binding. 22 As it is not known which binding mechanism applies to nucleotide interactions with 12 sites in the hexameric ClpB, we restrict our analysis to observing the shape of binding isotherms to obtain information on the effective nucleotide-binding capability of ClpB.…”
Section: Resultsmentioning
confidence: 99%
“…The 2 structures available now illuminate the transition from the ADP-to the apo-state. The ATP-loaded hexamer might look roughly similar as the nucleotide-free, but is presumably not 6-fold symmetric anymore, because it is unlikely that 6 ATP bind simultaneously and ATPs are bound with different affinities (24)(25)(26). Furthermore, the nucleotide induced subdomain closure within the AAA moiety would lead to a more compact, closed appearance.…”
Section: Discussionmentioning
confidence: 99%
“…Many other AAAϩ proteins have been crystallized only in the monomeric state and 6-fold-symmetric rings have been modeled frequently (22,23). Recent biochemical data, however, have demonstrated that at least in some nucleotide states the symmetry has to be lower, e.g., only maximally 4 ATP molecules bind to 1 hexameric ClpX or PAN or HslU particle (24)(25)(26).…”
mentioning
confidence: 99%
“…5). This mechanism would still work to some extent even if hydrolysis or ADP-ATP exchange does not occur in all six AAA domains simultaneously but rather in a probabilistic manner (14,37), as long as there is space for this domain movement. The lack of coupling between ATP hydrolysis and proteolysis in (⌬tm)FtsH constructs, and hence the inability in degrading 32 , could be explained by the absence of ''elastic springs'' formed by the transmembrane helices that would restrain the free movement of the AAA domains and possibly prevent them from being locked into one intermediate conformation on the reaction pathway.…”
Section: Discussionmentioning
confidence: 99%
“…All these substrates are degraded in an ATP-dependent manner where the energy is used for pulling the proteins out of the membrane and͞or unfolding and translocation. However, FtsH possesses only a weak unfoldase activity (13) and is not able to degrade stable proteins, contrary to other ATP-proteases like ClpXP (14).…”
mentioning
confidence: 99%